IMPLEMENTASI KURIKULUM MADRASAH DINIYAH DI ASRAMA PUTRI IV PONDOK PESANTREN DARUL ULUM JOMBANG - Eka Tusyana; Ulum Fatimatul Markhumah; Eka Yasinta Fatmawati (Tadrib: Jurnal Pendidikan Agama Islam, 2020)
The purpose of this research is to describe the implementation curriculum of Madrasah Diniyah Curriculum at Putri IV Dormitory Darul Ulum Islamic Boarding School in Jombang. Female Dormitory IV Darul Ulum Islamic Boarding School in Jombang is an Islamic educational institution that organizes a learning process that uses a structured Madrasah Diniyah curriculum. With the structured curriculum being implemented in Madrasah Diniyah, it is necessary to analyze the implementation of the education process. This research used field research method, of field research (Field research), namely research conducted with the intent to study intensively about the background of the current situation. The subjects in this study were the Principal of Madrasah Diniyah and Asatidz. Data collection instruments in this study used interviews, observation, and documentation. Analysis of the data used in the study are data reduction, data presentation, and drawing conclusions. The results of this study indicate that the implementation of the curriculum in Madrasah Diniyah at the Darul Ulum Islamic Boarding School in Jombang through several components, naely the implementation of the curriculum objectives of producing graduates who are of Islamic, populist quality, tafaqquh fi al-din and akhlaq al-karimah. The implementation of curriculum materials in Madrasah Diniyah is based on the salafiyah yellow books. The learning media implementation includes several tools such as laptops, LCD and loudspeakers. Implementation of learning methods used classical learning methods such as sorogan and bandongan. The implementation of the learning process in Madrasah Dinniyah places more emphasis on the lecture method based on the book's guidelines. Implementation of learning evaluation in Madarasah Dinniyah which refers to the written test, oral test (memorization) and practice that is carried out at the final Madrasah exam.